GENDER ASPECT OF SYMBOLIC SPACE (ON EXAMPLE OF RIVNE) - Івчик, Н. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The symbolic space of Rivne in its gender “reading” has been analyzed in the article. The object of the research is the monuments which have been established in this city during the existence of the USSR and after Ukraine become independent. It is affirmed that during the second part of the XX century the role of women in the Second World War was minimized, which, among other things, was reflected in sculptural compositions. Meanwhile, the participation of women in the struggle of the Ukrainian Insurgent Army is reflected only by one figure whose memory was honored by establishing a memorial plaque. The author states that in the formation of the symbolic space, Ukraine is partly a copy of the experience of the USSR: the removal of a significant role in its plots of heroism during the Second World War.